The Effect Of Corporate Governance On Effective Tax Rate With Profitability As A Moderating Variable - Harjanto, Atta Putra; Hajawiyah, Ain; Fredika, Afinda; Kiswanto, Kiswanto (Educoretax, 2024)
This study aims to analyze and describe the effect of corporate governance on the effective tax rate and the role of profitability in moderating the effect of corporate governance on the effective tax rate. The population of this research is non-financial companies registered as participants in the Corporate Governance Perception Index (CGPI) organized by The Indonesian Institute for Corporate Governance (IICG) in 2012-2021 with a total of 153 companies. Sampling in this study using non-random sampling technique with purposive sampling method and obtained a final sample of 67 companies. The data analysis technique used in this study is descriptive statistical analysis and inferential statistical analysis. The regression analysis method with moderating variables used in this study is the interaction test. The results of the study show that corporate governance has a negative effect on the effective tax rate. Leverage and size have no effect on the effective tax rate. Profitability has a negative effect on the effective tax rate. In addition, profitability cannot moderate the influence of corporate governance on the effective tax rate. The originality in this study is the existence of a profitability variable as a moderating variable and the measurement of corporate governance variables in this study uses a good corporate governance rating score based on the assessment of the corporate governance perception index (CGPI).